Impact of gene patents on diagnostic testing: a new patent landscaping method applied to spinocerebellar ataxia - Berthels, Nele (Nature Publishing Group, 2011)
Recent reports in Europe and the United States raise concern about the potential negative impact of gene patents on the freedom to operate of diagnosticians and on the access of patients to genetic diagnostic services. Patents, historically seen as legal instruments to trigger innovation, could cause undesired side effects in the public health domain. Clear empirical evidence on the alleged hindering effect of gene patents is still scarce. We therefore developed a patent categorization method to determine which gene patents could indeed be problematic. The method is applied to patents relevant for genetic testing of spinocerebellar ataxia (SCA). The SCA test is probably the most widely used DNA test in (adult) neurology, as well as one of the most challenging due to the heterogeneity of the disease. Typically tested as a gene panel covering the five common SCA subtypes, we show that the patenting of SCA genes and testing methods and the associated licensing conditions could have far-reaching consequences on legitimate access to this gene panel. Moreover, with genetic testing being increasingly standardized, simply ignoring patents is unlikely to hold out indefinitely. This paper aims to differentiate among so-called ‘gene patents' by lifting out the truly problematic ones. In doing so, awareness is raised among all stakeholders in the genetic diagnostics field who are not necessarily familiar with the ins and outs of patenting and licensing.